BSCI-23. TISSUE FACTOR SIGNALING ENHANCES METASTATIC BRAIN CANCER MALIGNANCY. (12th August 2019) - Unruh, Dusten; Mirkob, Snezana; James, C David; Horbinski, Craig
Abstract: Brain metastases are on the rise and remain one of the most refractory malignancies worldwide. Currently, the standard approach for therapy involves surgery and radiation. However, this approach usually produces only a modest increase in survival. We recently discovered that Tissue Factor (TF) strongly enhances the malignancy of gliomas via protease-activated receptor 2 (PAR2) signaling, though its role in brain metastases is not as well understood. In this study, we further explored the significance of TF in lung cancer brain metastases, showing that genetic and pharmacological targeting of TF-PAR2 signaling may decrease malignancy and increase the efficacy of radiotherapy. Studies were performed using patient-derived brain metastases coming from lung carcinoma. Markers of malignancy were measured by BrdU incorporation for cell proliferation, Matrigel-coated transwell migration, soft agar colony formation for anchorage-independent growth, limiting dilution assay for tumor initiation capacity, and clonogenic cell survival assay to measure radiation sensitivity. Low transcription of the TF gene is a favorable prognostic marker for overall survival in TCGA lung cancer patients (54.7 vs 41.9 months, P=0.0053), with 74% longer progression-free survival (102.7 vs 59.1 months, P=0.0012). TF knockdown significantly reduced tumor malignancy as determined by cell proliferation, invasion, colony formation, and in vivo growth. Conversely, TF overexpression increased tumor malignancy and promoted cancer stem-like behavior, as indicated by CD44 and CD133 expression, extreme limiting dilution assay, and anchorage-independent growth. A PAR2 antagonist, I-191, inhibited TF-mediated signaling and reduced cell proliferation by 51.3% (P< 0.001). TF knockdown and I-191 increased radiation sensitivity. Exogenous treatment of lung cancer cells with recombinant TF suppressed radiation-induced apoptosis, and this effect was blocked with I-191. These data show that TF-PAR2 signaling may represent a novel therapeutic strategy to reduce the malignancy of brain metastasis and increase the efficacy of radiation.